Detection of Adulteration of Ground Meat by Spectral-based Techniques and Artificial Intelligence (2020-2024) - Amir Kazemi; Asghar Mahmoudi; Mostafa Khojasteh Najand (مجله پژوهش‌های علوم و صنایع غذایی ایران)
Meat is a significant source of important nutrients and has a vital role in the human diet. Lack of monitoring of the quality and safety of meat can result in posing health threats. Determining safety through chemical methods is costly and time-consuming, without the ability to monitor in real-time. Therefore, nowadays assessing the quality of meat by applying spectral techniques such as spectroscopic and spectral imaging, considered as promising tools and these strategies have recently undergone swift advancements and garnered heightened public attention. Therefore, the purpose of the present review paper is to give an overview of the latest advancements in spectral methods for assessing ground meat safety. The basic working principles, fundamental settings, analysis process, and applications of these techniques are described. By investigating the practical utilization possibilities of spectral detection technologies in the evaluation of meat safety, researchers discussed the present challenges and upcoming research prospects. Furthermore, the newest advances in the application of artificial intelligence accompanied by the mentioned techniques were also discussed.